Estudio de la actividad analgésica en ratones Swiss sometidos a diferentes dosis de extracto hidroalcohólico al 30% de raíz de Eclipta alba - Pinto, Wagner de Jesus; Treto, Rafael Rodriguez; Vieira, Lukas; Graebner, Ilmar Bernardo (Revista de Ciências Médicas e Biológicas, 2017)
Introduction: the Eclipta alba is kwoned as ``agrião do brejo´´ in Brazil. Etnomedical studies consider it as antinflamatory and analgesic plant. Objective: To determine the excitation`s threshold of nociceptive system in mice trated whith diferents doses of hydroalcoholic stratum, 30% of Eclipta alba dead roots. Methodology: were used 42 Swiss mice bewteen 8-10 weeks old, constant ambiental temperature of 25ºC and water / food “ad libitum”. The analgesic activitiy was determined by the ``hot plate´´ test and the analgesic indicator was the time`s reaction of each animal. Result and Discussion: analgesic action of hydroalcoholic stratum, 30% of Eclipta alba dead root, was confirmed at 60, 90 and 120 minutes. This activity was similar as paracetamol analgesic action (12.5 mg.kg-1). The analgesic efect of paracetamol was increasing for 150 minutes. The prostaglandins inhibition synthesis may be a cause of the analgesic action. Antioxidant effect of phenol and polyphenols compounds presents in the hydroalcoholic stratum, 30% of Eclipta alba dead root and the inhibition of phospholipase A2 by flavonois compounds presents in the stratum too, may be explain the results of this paper, througt the low level of prostaglandins. Conclusion: the hydroalcoholic stratum, 30% of Eclipta alba dead root (500 and 250 mg kg-1) and paracetamol (12.5 mg.kg-1) showed a similar analgesic activity bewteen 60 and 120 minutes.